Islamophobia: Discrimination Against Muslims in America in Attempt to Maintain Global Hegemony - Nisa, Sayyidah Ilman (Universitas Muhammadiyah Yogyakarta, 2022)
Islamophobia emerged in 1992 and has spread since9/11 when a terrorist attack brought down the Twin Towersof the World Trade Center (WTC) in New York. In itshistory, America is the inheritor of the